2019
DOI: 10.1002/jcb.29182
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR‐675‐5p induced by lncRNA H19 was associated with tumor progression and development by targeting tumor suppressor p53 in non–small cell lung cancer

Abstract: Lung cancer is the main cause of cancer‐related death, and the proportion of non–small cell lung cancer (NSCLC) on lung cancer is 85%, while more than 80% lung cancer patients are diagnosed with chronic obstructive pulmonary disease (COPD). In this study, we aimed to explore the potential mechanism of COPD induced NSCLC. Luciferase assay and reverse transcription‐polymerase chain reaction (RT‐PCR) were conducted to study the regulatory relationship between P53 and microRNA‐675 (miR‐675). Real‐time PCR, Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 39 publications
(78 reference statements)
0
45
0
Order By: Relevance
“…The competing endogenous (ce)RNA hypothesis suggests that the expression of lncRNAs controls the mRNAs levels via sponging miRNAs (14). Several lncRNAs have been reported to be oncogenes or tumor suppressors in NSCLC (15)(16)(17). For instance, Yang et al (18) indicated that lncRNA insulin-like growth factor binding protein 4-1 was significantly upregulated in lung cancer and promoted tumor cell metabolism to facilitate cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…The competing endogenous (ce)RNA hypothesis suggests that the expression of lncRNAs controls the mRNAs levels via sponging miRNAs (14). Several lncRNAs have been reported to be oncogenes or tumor suppressors in NSCLC (15)(16)(17). For instance, Yang et al (18) indicated that lncRNA insulin-like growth factor binding protein 4-1 was significantly upregulated in lung cancer and promoted tumor cell metabolism to facilitate cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that reduced H19 and miR675 expression led to increased p53 protein expression, which regulates cell apoptosis [25]. Our data showed that mutation of the regions upstream of the m 6 A modification site inhibited miR675 and H19 expression, inducing cell apoptosis, possibly through the p53 protein.…”
Section: Discussionmentioning
confidence: 52%
“…So far, 10 polymorphisms in H19 have been identi ed as predisposing factors to various cancer types, among which the rs217727 has been most frequently studied, followed by rs2839698 [45]. H19 plays an essential role in the tumor progression of breast cancer [15], bladder cancer [46], gastric cancer [17], and other tumors [20,47,48], other than that, mutations in the H19 gene coding sequence are also closely related to tumors, despite unknown regulatory mechanisms [12,49]. The following evidence suggests that SNPs may affect the expression and function of the H19 gene.…”
Section: Discussionmentioning
confidence: 99%
“…More and more evidence indicates that the H19 gene is essential for human tumor growth from different biological processes [15]. Studies have shown that the H19 gene was upregulated in lung cancer, gastric cancer, colon cancer, retinoblastoma, thyroid cancer and breast cancer [15][16][17][18][19][20]. However, the up-regulated expression of the H19 gene can inhibit pituitary tumor cell proliferation in vitro and in vivo [21].…”
Section: Introductionmentioning
confidence: 99%